Strength and Stiffness of Cross Laminated Timber (CLT) panels produced with Pinus and Eucalyptus: experimental and analytical comparisons - Pereira,Marcos Cesar de Moraes (2019)
ABSTRACT The CLT is a building material that comes mainly used in Europe where it was developed. Lightweight, sturdy and eco-friendly, this material has become one of the most important constructive methods in the world. CLT are panels formed by layers of wood glued to each other orthogonally, always in odd numbers, symmetrical with respect to the central layer. The dimensions can vary from 50 to 500 mm in thickness, and depend on the application, which can be a slab or wall element, the width and length are adjustable, being able to produce up to 20 meters in length. This work presents tests and results obtained in two types of CLT panels produced in a laboratory. One panel made with Pinus taeda and MUF (melamine urea formaldehyde) adhesive and other one made Eucalyptus urograndis with PU (polyurethane) adhesive. The objective was to evaluate the stiffness and to through the analytical method using the Analytical Design Method (γ-method), and through experimental tests in the laboratory, comparing the values obtained in each method. In the experimental test, the Eucalyptus panel obtained better strength and stiffness than Pinus panel, and in analytical calculation using the Analytical Design Method (γ-method), obtained Elastic Modulus (MOE) values slightly above experimental values, and stiffness values (EI) considerably below experimental values. Concluded that the Cross Laminated Timber produced with Pinus and Eucalyptus planted in Brazil obtained resistance and stiffness considered suitable for structural use and showed that it could be a new alternative of constructive material to be used in the country.